(untitled) (2014)
Rotavirus is recognized worldwide as the main and most important viral pathogen associated with diarrhea in children while norovirus is considered the second cause of epidemic diarrhea in developed countries. Here, we present a comparative study on the prevalence of rotavirus and norovirus in two regions of Colombia: Chocó and Cundinamarca. Five hundred and thirty stool samples were collected; 330 in Cundinamarca and 200 in Chocó. In the sample set from Chocó, 6 % of the samples presented rotavirus and 8 % norovirus; meanwhile, 9.7 % of the samples from Bogotá presented rotavirus and 9 % norovirus. These results show that, in some regions of Colombia, the prevalence of norovirus is similar or slightly higher than rotavirus. This is a tendency that should be examined in other non-developed countries as it suggests that the presence of norovirus should also be under surveillance.